Stressed and strained state of layered cylindrical shell under local convective heating - Мусій, Р. С.; Жидик, У. В.; Турчин, Я. Б.; Свідрак, І. Г.; Байбакова, І. М.; Musii, R. S.; Zhydyk, U. V.; Turchyn, Ya. B.; Svidrak, I. H.; Baibakova, I. M. (Видавництво Львівської політехніки, 2021)
Досліджено напружено-деформований стан шаруватої композитної кругової циліндричної оболонки за локального нагрівання довкіллям через конвективний теплообмін. Для цього використано рівняння шестимодальної теорії термопружності і двовимірне рівняння теплопровідності неоднорідних анізотропних оболонок. Методами інтегральних перетворень Фур’є і Лапласа знайдено розв’язок нестаціонарної задачі теплопровідності та квазістатичної задачі термопружності для скінченної шарнірно опертої ортогонально армованої оболонки симетричної структури. Числові результати наведено для тришарової оболонки

The stress-strain state of a layered composite cylindrical shell under local heating by the environment due to convective heat exchange has been studied. The equation of the six-modal theory of thermoelasticity and the two-dimensional equation of thermal conductivity of inhomogeneous anisotropic shells are used for this purpose. The solution of the nonstationary heat transfer problem and the quasi-static thermoelasticity problem for a finite hinged orthogonally reinforced shell of symmetric structure is found by the methods of integral Fourier and Laplace transforms. Numerical results are given for the three-layer shell.
Напружено-деформований стан шаруватої циліндричної оболонки за локального конвективного нагрівання
Keywords: термопружність; шаруваті матеріали; температурне навантаження; циліндрична оболонка; thermoelasticity; layered materials; temperature loading; cylindrical shell